Immunization Strategies Producing a Humoral IgG Immune Response against Devil Facial Tumor Disease in the Majority of Tasmanian Devils Destined for Wild Release - Pye, Ruth; Patchett, Amanda; McLennan, Elspeth; Thomson, Russell; Carver, Scott; Fox, Samantha; Pemberton, David; Kreiss, Alexandre; Baz Morelli, Adriana; Silva, Anabel; Pearse, Martin J.; Corcoran, Lynn M.; et al. (Frontiers in Immunology, 2018)
Devil facial tumour disease (DFTD) is renowned for its successful evasion of the host immune system. Down regulation of the major histocompatabilty complex class I molecule (MHC I) on the DFTD cells is a primary mechanism of immune escape. Immunisation trials on captive Tasmanian devils have previously demonstrated that an immune response against DFTD can be induced, and that immune mediated tumour regression can occur. However, these trials were limited by their small sample sizes. Here we describe the results of two DFTD immunisation trials on cohorts of devils prior to their wild release as part of the Tasmanian Government’s Wild Devil Recovery project. 95% of the devils developed anti-DFTD antibody responses. Given the relatively large sample sizes of the trials (N=19 and N=33), these responses are likely to reflect those of the general devil population. DFTD cells manipulated to express MHC-I provided the antigenic basis of the immunisations in both trials. Although the adjuvant composition and number of immunisations differed between trials, similar anti-DFTD antibody levels were obtained. The first trial comprised DFTD cells and the adjuvant combination of ISCOMATRIX™, polyIC and CpG with up to four immunisations given at monthly intervals. This compared to the second trial whereby two immunisations comprising DFTD cells and the adjuvant combination ISCOMATRIX™, polyICLC (Hiltonol®) and imiquimod were given a month apart, providing a shorter and therefore more practical protocol. Both trials incorporated a booster immunisation given up to five months after the primary course. A key finding was that devils in the second trial responded more quickly and maintained their antibody levels for longer compared to devils in the first trial. The different adjuvant combination incorporating the RNAase resistant polyICLC and imiquimod used in the second trial is likely to be responsible. The seroconversion in the majority of devils in these anti-DFTD immunisation trials was remarkable, especially as DFTD is hallmarked by its immune evasion mechanisms. Microsatellite analyses of MHC revealed that some MHC-I microsatellites correlated to stronger immune responses. These trials signify the first step in the long term objective of releasing devils with immunity to DFTD into the wild.